Effect of photodynamic therapy on the extracellular matrix and associated components - Pazos,M.d.C. (2007)
In many countries, photodynamic therapy (PDT) has been recognized as a standard treatment for malignant conditions (for example, esophageal and lung cancers) and non-malignant ones such as age-related macular degeneration and actinic keratoses. The administration of a non-toxic photosensitizer, its selective retention in highly proliferating cells and the later activation of this molecule by light to form reactive oxygen species that cause cell death is the principle of PDT. Three important mechanisms are responsible for the PDT effectiveness: a) direct tumor cell kill; b) damage of the tumor vasculature; c) post-treatment immunological response associated with the leukocyte stimulation and release of many inflammatory mediators like cytokines, growth factors, components of the complement system, acute phase proteins, and other immunoregulators. Due to the potential applications of this therapy, many studies have been reported regarding the effect of the treatment on cell survival/death, cell proliferation, matrix assembly, proteases and inhibitors, among others. Studies have demonstrated that PDT alters the extracellular matrix profoundly. For example, PDT induces collagen matrix changes, including cross-linking. The extracellular matrix is vital for tissue organization in multicellular organisms. In cooperation with growth factors and cytokines, it provides cells with key signals in a variety of physiological and pathological processes, for example, adhesion/migration and cell proliferation/differentiation/death. Thus, the focus of the present paper is related to the effects of PDT observed on the extracellular matrix and on the molecules associated with it, such as, adhesion molecules, matrix metalloproteinases, growth factors, and immunological mediators.